Odpowiedzi

2009-10-22T17:50:10+02:00
1.0.27
2. 5 i 11/32
3. 3,75
4. 8 i 2/3
1 2 1
Najlepsza Odpowiedź!
2009-10-22T20:42:46+02:00
(2,2 - 1⅔) * 0,9 = (11/5 - 1⅔) * 9/10 = (33/15 - 25/15) * 9/10 = 8/15 * 9/10 = 12/25
3/4 z tego wyrażenia to:
3/4 * 12/25 = 9/25

2 * 3,5 + ½ * 0,25 = 7 + 0,125 = 7,125
3/4 z tego wyrażenia to:
3/4 * 7,125= 3/4 * 57/8 = 171/32 = 5 11/32

4,5 * 1⅔ - 3,75 = 9/2 * 5/3 - 15/4 = 7,5 - 3,75=3 3/4
3/4 z tego wyrażenia to: 3/4 * 15/4= 45/16 = 2 3/16


10 - 10/27 : 5/6 = 10 - 10/27 * 6/5 = 10 - 12/27= 10 - 12/27= 9 15/27
3/4 z tego wyrażenia to:
3/4 * 258/27= 129/18= 7 1/6